Kształcenie zdalne – nieuprawniony entuzjazm czy pierwszy milowy krok? - Przybyła, Mariusz (Rocznik Pedagogiczny, 2021)
Nowadays it is difficult to talk about the real and virtual world in the context of contemporary students. Perhaps even talking about „on-line” vs „off-line” is a thing of the past, since some of us are always online. Remote learning changes the approach to school and extracurricular education and affects all levels of education. An important aspect of considerations on school and academic e-learning is so called the bottom-up push, i.e. the involvement of enthusiasts discovering the se- crets of e-learning platforms in front of their pupils and the willingness of these pupils and students. Observing the changes implemented in the education system over the last decades, we can honestly state, that these were rather sham movements, unable to change the class-lesson system and its el- ements burdening us as the subjects of the education process. What happened, then? What powers have changed school and academic education, so that we have found ourselves in the digital world? Have we started using mobile solutions? Can we conduct online classes? Is this a necessary evil or an opportunity for tomorrow (for universities/schools, students/pupils, lecturers/teachers and for modern, constantly learning societies)? Distance learning contributes to creating new spaces for educational interactions. It enables both mass and individual education in synchronous and asyn- chronous modes.